Rapid characterization of feline leukemia virus infective stages by a novel nested recombinase polymerase amplification (RPA) and reverse transcriptase-RPA - Sitthichok Lacharoje (Nature Portfolio, 2021)
Abstract Feline leukemia virus (FeLV) is a major viral disease in cats, causing leukemia and lymphoma. The molecular detection of FeLV RNA and the DNA provirus are important for staging of the disease. However, the rapid immunochromatographic assay commonly used for antigen detection can only detect viremia at the progressive stage. In this study, nested recombinase polymerase amplification (nRPA) was developed for exogenous FeLV DNA provirus detection, and reverse transcriptase polymerase amplification (RT-RPA) was developed for the detection of FeLV RNA. The approaches were validated using 108 cats with clinicopathologic abnormalities due to FeLV infection, and from 14 healthy cats in a vaccination plan. The nRPA and RT-RPA assays could rapidly amplify the FeLV template, and produced high sensitivity and specificity. The FeLV detection rate in regression cats by nRPA was increased up to 45.8% compared to the rapid immunochromatographic assay. Hence, FeLV diagnosis using nRPA and RT-RPA are rapid and easily established in low resource settings, benefiting FeLV prognosis, prevention, and control of both horizontal and vertical transmission.